CONFLICTS AND DEMOCRACY IN ETHNICALLY COMPLEX SOCIETIES AND ROLE OF MEDIA: THE CASE OF YUGOSLAVIA IN 1999 : Intervention, victims and stereotypes - Penezić, Slobodan M.; Cvijović, Milija Ž. (NBP. Nauka, bezbednosti, policija, 2020)
The text herein is inspired by Hans Magnus Enzensberger and his writings about "nucleated" civil wars initiated by interethnic differences. Placing his thoughts in context of media, he sees those wars as a spectacle which makes the audience perceive it as a moral problem. The paradigm for interpreting these conclusions may also be the influence of media on perception of events in Yugoslavia in 1999. The starting questions are, therefore, directed towards analysing the validity of such conclusions, which we try to do by explaining the nature of relationship between wars and media influence, as well as the origin of stereotypes about the Balkans - their multiplication with start of conflict and influence of the media on it. In doing so, we can also notice the misconceptions and the effects they produced; with parallel analysis of the essential principles of journalistic reporting, but also a clear disregard for them, with the aim to show their causes too. This makes it possible to deduce what was the effect of reporting and how much it led to problem-solving and transformation of Balkan societies, or it caused new stereotyping and problems. In this way, all the pointlessness of the conflict and NATO's interventions as well are demonstrated, and the conclusion of analysis become a confirmation for Enzensberger's thinking.
Keywords: Yugoslavia, NATO bombing, media reporting, journalism ethics, the Balkans, interethnic conflicts